Study of resistance of spring barley genotypes to zinc and cadmium (Eurasian Journal of Ecology, 2019)
The most important task of ecology today and in the future is the control of the content of chemical elements in plant products, the possibility of its regulation. In this regard, the study of resistanceto cadmium and zinc of different genotypes of barley in the conditions of model experience was conducted. The aim of the work is to identify metal – resistant genotypes for their further study on yieldand resistance to climatic conditions of the environment in the field experiment. The paper studied thegrowth parameters of biometric indicators and the accumulation of dry biomass, as well as the contentof the studied metals in seedlings under environmental pollution by cadmium ions (40 mg/l) and zinc(400 mg/l). The data obtained showed that different genotypes respond differently to adverse effects ofcadmium and zinc ions. Differences are revealed both in growth parameters and in the degree of accumulation of the studied metals in spring barley plants. The results of the experiment revealed the root stability of the studied forms, as well as resistance to the entry of zinc and cadmium into the abovegroundorgans. The identified stable genotypes are recommended for further study of their yield and survival inthe weather conditions of the East Kazakhstan region in field experiments to identify promising forms foragricultural production.Key words: zinc, cadmium, barley, dry biomass accumulation, metals accumulation, stability.